FEMINISME DALAM TASAWUF: SEBUAH TINJAUAN LITERATURE REVIEW - Deni Irawati; Nunu Burhanuddin (CV. Adiba Aisha Amira, 2023)
Islamic feminism seeks to empower women spiritually and morally, eradicate injustice,and promote gender equality in all areas of life. Humans, both men and women, have equal opportunities to obtain maqamat and ahwal in order to reach true Sufis, as stated in Sufism literature. This article aims to find out and understand about feminist thinking in Sufism in the modern era. This article uses a literature review approach. Literature search was carried out online through Google Scholar which was limited from 2012- 2022 with a search process using the keywords